Chemical Intolerance Is Associated With Altered Response Bias, not Greater Sensory Sensitivity. (December 2020) - Andersson, Linus; Sandberg, Petra; Åström, Elisabeth; Lillqvist, Moa; Claeson, Anna-Sara
Chemical intolerance is a surprisingly prevalent condition or affliction characterized by adverse reactions to low levels of chemical, often odorous stimulation. Sufferers often assume that their plight is due to an uncommon sensory acuteness, yet studies repeatedly fail to reveal altered detection thresholds. Here, we investigated whether self-reported chemical intolerance is associated with altered sensory sensitivity or response bias. The sensory acuity (sensitivity; A) and sensory decision rule (criterion; B) to n -butanol was assessed using the method of constant stimuli in 82 participants with different degrees of chemical intolerance (low to high). Higher self-reported chemical intolerance was associated with a lower criterion, but not with sensitivity.